Is convergence in desires possible? A critical assessment of Michael Smith’s moral realism [A convergência em desejos é possível? Uma avaliação crítica do realismo moral de Michael Smith] - Dalsotto, Lucas Mateus (Princípios: Revista de Filosofia (UFRN), 2018)
In this paper, I intend to evaluate if Michael Smith’s account in support of a substantive convergence among agents’ idealized desires is compelling enough to show us that such agreement would be possible. Smith claims that moral argument tends to elicit moral agreement among agents’ opinions and that this gives us a reason to believe that there would be a convergence in desires under conditions of full rationality. He maintains that the best explanation of that historical tendency is our substantive convergence upon a set of extremely unobvious a priori moral truths. However, I think he fails to provide us with any convincing reason to expect that a substantive convergence would be attained. I argue Smith’s consensus on moral issues is less probable than disagreement if there is no normative standard for the correctness of the desires we would want ourselves to have in conditions of full rationality. If my argument succeeds it follows that Smith’s account is a sort of error theory of normative reasons, rather than a realistic one. [Neste artigo, pretendo avaliar se a abordagem de Michael Smith apoiando uma convergência substantiva entre os desejos idealizados dos agentes é convincente a ponto de nos mostrar que tal acordo seria possível. Smith afirma que a discussão moral tende a gerar acordo moral entre as opiniões dos agentes e que isso nos dá uma boa razão para acreditarmos que haverá uma convergência em desejos sob condições de racionalidade plena. Ele defende que a melhor explicação dessa tendência histórica é nossa convergência substantiva a respeito de um conjunto de verdades morais a priori pouco óbvias. Contudo, penso que ele falha em oferecer qualquer razão convincente para esperarmos que uma convergência substantiva seria alcançada. Argumento que o consenso de Smith sobre questões morais é menos provável do que o desacordo caso não haja nenhum padrão normativo de correção dos desejos que esperaríamos ter em condições de racionalidade plena. Se meu argumento é bem-sucedido, segue-se que a abordagem de Smith é um tipo teoria do erro de razões normativas, ao invés de um tipo de teoria realista.]